Visualization of Curriculum Based on the Degree of Relevance among Subjects and Its Utilization - FUJINO, Tomokazu (Japan Journal of Educational Technology, 2024)
The purpose of this study is to establish a method to support university staff in self-assessment and improvement of curricula and to support students in selecting courses, by focusing on the relevance of courses in the curricula (educational programs) of higher education institutions. First, we propose a method for developing inter-course relevance data and an indirect relevance index between courses based on the data. From these indices, the degree of influence of subjects on the curriculum as a whole can be obtained. Using these indices, we show how to visualize the curriculum from various perspectives. The applicability of this method is discussed through an example of the author's department.